P816 The efficacy of an over the counter multivitamin and mineral supplement to prevent opportunistic infections in patients with inflammatory bowel disease in remission. (30th January 2023) - Laheij, R; van Knippenberg, Y; Heil, A; Mannaerts, B; Bruin, K; Lutgens, M; Sikkema, M; de Wit, U; Laheij, R
Abstract: Background: Patients with inflammatory bowel disease (IBD) treated with immunomodulators or biological therapy are at increased risk of infections. Malnutrition and vitamin or mineral deficiencies are common among patients with IBD. The results of various studies have indicate that vitamin deficiencies might increase the risk of infections. Methods: Single-centre, randomized, double-blinded, placebo-controlled clinical trial to compare a multivitamin and mineral supplement (vitamin group) versus identical in appearance placebo (placebo group). Patients with Crohn's disease or ulcerative colitis using immunomodulators and/or biological therapy without vitamin deficiency were considered for participation in our study. Participants were asked to take a daily multivitamin and mineral supplement or placebo and report the occurrence of infections during a 24 weeks period of follow up. The primary endpoint of this study was the difference in incidence of infection between the two groups measured by a validated questionnaire, the revised version of the ID screen to assess infection 13 . Randomization was conducted by using computer generated random numbers with an allocation ratio of 1:1 to vitamin supplement or placebo in blocks of 8 and stratified according to type of IBD.Results Between July 2020 and February 2021, 320 patients were randomized. Treatment arms consisted out of 162 and 158 for vitamin and placebo, respectively. Both groups showed similarity in patient characteristics. All patients were included in the intention-to -Treat (ITT), 265 patients in the per protocol (PP) (compliance >80%) analyses. For both groups, 107 patients reported an infection during the 24 weeks follow up period (Unadjusted Odds Ratio: 0.93 (95% confidence interval: 0.56-1.48). In the vitamin group, 32 patients received antibiotics for an infection compared with 21 patients in the placebo group (Unadjusted Odds Ratio: 1.61 (95% confidence interval: 0.88-2.93). 166 patients in the PP analysis reported an infection (Unadjusted Odds Ratio: 0.91 (95% confidence interval: 0.55-1.50), 23 reported a serious infection (Unadjusted Odds Ratio: 2.57 (95% confidence interval: 1.02 -6.46). None of the patients was hospitalized due to serious infection. Conclusion: An over the counter multivitamin and mineral supplement did not reduce the risk of infection for patients with IBD in remission with immunomodulators and/or biological therapy.